Paediatric oncology short learning programmes for nurses: a scoping review - Apatsa Selemani; Maureen Daisy Majamanda; Felix Chisoni; Irene Kearns; Johanna Maree (BMJ Open)
Objective This scoping review aimed to map the content, duration, delivery methods and modes of assessment for paediatric oncology nursing education and training programmes.Design Scoping review.Data sources Published articles were retrieved from Cumulative Index to Nursing and Allied Health Literature, Dimensions, Embase, PubMed and Scopus. Additional articles were identified from the reference list of the included studies.Eligibility criteria Articles that described or reported on a paediatric oncology nursing education and training programme, from any setting, published in English from 2012 to 2022.Data extraction and synthesis Two reviewers independently screened the titles, abstracts and full texts. Data were extracted using a standardised data extraction tool. Content analysis using basic coding of data was performed. The findings are presented in figures and tables, and the results are described narratively.Results This review included 15 articles. Content identified for paediatric oncology education and training programmes included supportive care, chemotherapy, overview of paediatric oncology, management of venous access devices, oncological emergencies, nursing considerations, infection prevention and control, paediatric cancers, patient and family education, communication, ethical legal considerations, grief and bereavement, and overview of haematological cancers. Didactic methods used included traditional face-to-face and virtual approaches to deliver theoretical and practical content. The duration of the programmes ranged from 2 hours to 6 months. Both qualitative and quantitative methods of assessment were used before, during and after the training.Conclusion This review offers valuable insights for the development of paediatric oncology education and training programmes for nurses. It provides comprehensive guidance on key content, duration, delivery methods and modes of assessment. However, there is a need to consider context-specific issues and availability of resources when developing the programmes to ensure relevance and sustainability.Study registration Open Science Framework (https://doi.org/10.17605/OSF.IO/X3Q4H).